Physical activity, brain tissue microstructure, and cognition in older adults. - Robert J Dawe; Lei Yu; Sue E Leurgans; Bryan D James; Victoria N Poole; Konstantinos Arfanakis; Julie A Schneider; David A Bennett; Aron S Buchman (PLoS ONE)
Objective To test whether postmortem MRI captures brain tissue characteristics that mediate the association between physical activity and cognition in older adults. Methods Participants (N = 318) were older adults from the Rush Memory and Aging Project who wore a device to quantify physical activity and also underwent detailed cognitive and motor testing. Following death, cerebral hemispheres underwent MRI to quantify the transverse relaxation rate R2, a metric related to tissue microstructure. For analyses, we reduced the dimensionality of the R2 maps from approximately 500,000 voxels to 30 components using spatial independent component analysis (ICA). Via path analysis, we examined whether these R2 components attenuated the association between physical activity and cognition, controlling for motor abilities and indices of common brain pathologies. Results Two of the 30 R2 components were associated with both total daily physical activity and global cognition assessed proximate to death. We visualized these components by highlighting the clusters of voxels whose R2 values contributed most strongly to each. One of these spatial signatures spanned periventricular white matter and hippocampus, while the other encompassed white matter of the occipital lobe. These two R2 components partially mediated the association between physical activity and cognition, accounting for 12.7% of the relationship (p = .01). This mediation remained evident after controlling for motor abilities and neurodegenerative and vascular brain pathologies. Conclusion The association between physically activity and cognition in older adults is partially accounted for by MRI-based signatures of brain tissue microstructure. Further studies are needed to elucidate the molecular mechanisms underlying this pathway.